2021
DOI: 10.3390/cells10020345
|View full text |Cite
|
Sign up to set email alerts
|

Human Genetic Variation Influences Enteric Fever Progression

Abstract: In the 21st century, enteric fever is still causing a significant number of mortalities, especially in high-risk regions of the world. Genetic studies involving the genome and transcriptome have revealed a broad set of candidate genetic polymorphisms associated with susceptibility to and the severity of enteric fever. This review attempted to explain and discuss the past and the most recent findings on human genetic variants affecting the progression of Salmonella typhoidal species infection, particularly toll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 132 publications
(186 reference statements)
1
5
0
Order By: Relevance
“…Also, the study of Ma et al . (16) was consistent with the present study that showed no association between typhoid fever severity and polymorphism in the NRAMP1 gene when they studied human genetic variation influences enteric fever progression in Malaysia. The change in the SNP from G to C will lead to a change in the type of amino acid produced and included in the protein structure of the NOD2 receptor, and it is discussed whether the new amino acid will change the structure of the receptor and its functional ability.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Also, the study of Ma et al . (16) was consistent with the present study that showed no association between typhoid fever severity and polymorphism in the NRAMP1 gene when they studied human genetic variation influences enteric fever progression in Malaysia. The change in the SNP from G to C will lead to a change in the type of amino acid produced and included in the protein structure of the NOD2 receptor, and it is discussed whether the new amino acid will change the structure of the receptor and its functional ability.…”
Section: Discussionsupporting
confidence: 93%
“…The results of the distribution of S. typhi according to age revealed that the highest number of typhoid fever infection was located in the age group (1-10) years that represented 20 patients with a percentage (38.46%) of the total number, followed by (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) years that showed 17 patients with a percentage (32.70%) , whereas the last three groups seemed almost equal in the age groups (21-30)years with 6 (11.60%), and (31-40) years that showed 5 (9.60%), lastly 4(7.70%) for the age group (41-50) years with a highly significant difference (P≤ 0.01), as shown in Table (4).…”
Section: Target Genementioning
confidence: 99%
“…Several studies have initiated identification of host chromosomal loci responsible for resistance to acute S . Typhi in man [ 135 , 136 , 137 , 138 ], S. Typhimurium in mice [ 139 ] and Salmonella in chickens [ 140 , 141 ].…”
Section: Is There a Clear Host Genetic Element That Contributes To The Development Of The Carrier State?mentioning
confidence: 99%
“…Slc11a1 is not associated with typhoid susceptibility in man [ 138 ] although it, aided by other host genes, is a prerequisite for establishing the carrier state in mice with virulent strains of S . Typhimurium [ 4 , 85 , 142 ].…”
Section: Is There a Clear Host Genetic Element That Contributes To The Development Of The Carrier State?mentioning
confidence: 99%
“…In the 21 st century, enteric fever is responsible for causing a significant number of mortalities in high risk regions of the world [16]. The prevalence of typhoid fever is alarmingly high with approximately 200,000 deaths each year in developing countries [25].…”
Section: Introductionmentioning
confidence: 99%